The Relationship between Professional Behavior and the Quality of Internal Audit of the North Sumatra Provincial Government - Yulisfan, Yulisfan; Nasution, M.Irsan (International Conference on Sciences Development and Technology, 2023)
This study aims to investigate the relationship between internal auditors' professional behavior and internal audit quality in the North Sumatra Provincial Government. Internal auditors' professional behavior, which includes ethics, independence, and integrity, is considered a critical factor that can affect audit quality. This study used a survey method and data were collected through questionnaires distributed to internal auditors who served in the provincial government agencies. The results of data analysis using descriptive statistical techniques and correlation analysis showed a significant positive relationship between the professional behavior of internal auditors and internal audit quality. It was found that internal auditors who exhibit high professional behavior tend to produce better internal audit quality. This study contributes to the practical and theoretical understanding of the factors that influence internal audit quality in the context of provincial government. The implications of the findings may assist decision makers in improving internal audit practices through enhancing the professional behavior of internal auditors. In addition, this study can serve as a foundation for further research in the field of government auditing and accounting.